2020
DOI: 10.1142/s1793292020500113
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of MoS2 Hierarchical Nanostructures as Electrodes for Capacitor with Enhanced Pseudocapacitive Property

Abstract: In this work, the 3D porous hierarchical MoS2 nanostructures were prepared via a simple hydrothermal deposition method only utilizing titanium (Ti) mesh as a substrate. The as-synthesized uniform MoS2 flower-like nanostructures were assembled by nanosheets composed of several stacking layers. The curved and rough surface of cylindrical Ti wire was beneficial to assembly of MoS2 nanosheets into hierarchical architectures. Moreover, the electrochemical performance of the as-prepared MoS2 nanostructured electrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Galvanostatic charge-discharge (GCD) tests were performed between 0 and 1 V at different current densities. Meanwhile, electrochemical impedance spectroscopy (EIS) was performed at 1.0 × 10 −2 and 1.0 × 10 5 Hz at an open circuit voltage. Cycling stability was investigated by GCD at a current density of 10 mA cm −2 .…”
Section: Evaluation Of Electrochemical Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Galvanostatic charge-discharge (GCD) tests were performed between 0 and 1 V at different current densities. Meanwhile, electrochemical impedance spectroscopy (EIS) was performed at 1.0 × 10 −2 and 1.0 × 10 5 Hz at an open circuit voltage. Cycling stability was investigated by GCD at a current density of 10 mA cm −2 .…”
Section: Evaluation Of Electrochemical Performancementioning
confidence: 99%
“…In this aspect, carbon cloth (CC) as a carbon fiber textile substrate has the advantages of high electrical conductivity and light weight. 3 In comparison with metal substrates such as nickel foam 4 and titanium mesh, 5 the good mechanical properties, flexibility and chemical stability of the CC substrate make it a promising material for applications in portable electronic devices. However, the poor hydrophilicity, low specific surface area and inherent electric double-layer capacitance of CC itself also limit its ability to achieve high capacitance.…”
Section: Introductionmentioning
confidence: 99%
“…97 Further, the specic capacitances of 90.1, 225, and 218.4 F g À1 at the current density of 1 A g À1 have been reported for sponge-like MoS 2 , ower-like mesoporous MoS 2 , and irregular MoS 2 nanosheet, respectively. [101][102][103] Wang et al synthesized 3D ower-like MoS 2 electrode materials through the hydrothermal method by varying the duration of treatment in the autoclave. The calculated specic capacitances revealed that the MoS 2 -16 electrode (treatment time 16 h) had a higher specic capacitance of 518.7 F g À1 at a current density of 1 A g À1 than those of MoS 2 -8 (treatment time 8 h) and MoS 2 -24 (treatment time 24 h) electrodes.…”
Section: Molybdenum Suldementioning
confidence: 99%
“…97 Further, the specific capacitances of 90.1, 225, and 218.4 F g −1 at the current density of 1 A g −1 have been reported for sponge-like MoS 2 , flower-like mesoporous MoS 2 , and irregular MoS 2 nanosheet, respectively. 101–103…”
Section: Energy Storage In Metal Sulfides-based Capacitorsmentioning
confidence: 99%